Moral Values of War in Islamic History: A Reading in the Document of the Reign of Imam al-Salt bin Malik al-Kharusi (3 AH/9 CE) - AL- Sawafi , Said Bin Rashid (Dirasat: Shari'a and Law Sciences, 2021)
This study aims to demonstrate the moral values of war in Islamic history through the document of Imam al-Salt bin Malik al-Kharousi (3 AH / 9 CE) to his army on the island of Socotra. It also aims to reveal models for the practical application of the teachings of Islam and highlight the ethics of war in Islam through the content of the document of the reign of Imam Salat Bin Malik and the statement of the moral values of the objectives of war and its controls in Islam. The study relied on the inductive approach in contemplating the document of Imam Al-Salt, and the descriptive approach in presenting the study's vocabulary, and the analytical method in some other important issues. The most important findings of the study are as follows. Islam approved war for goals necessitated by the human interest. Islam made the legality of war linked to moral values, and laid the foundations, principles and restrictions that regulate them. The study explains that the document of Imam Salt bin Malik al-Kharusi to his army is one of the most civilized models for applying the moral values of war in Islamic history. It is a practical application of what is mentioned in the Holy Qur’an and the Prophet’s Sunnah on how to deal with non-Muslims in peace and war.